Pengaruh kepemimpinan guru dalam mengembangkan moralitas siswa melalui pembentukan karakter - Amalia, Citra; Muhajir; Aba, Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine teacher leadership, student morality, and the influence of teacher leadership on developing student morality through character education at SMA Negeri 3 Bantaeng. A mixed methods approach was used, with data collected through questionnaires (quantitative) and observation, interviews, and documentation (qualitative). The results indicate that teacher leadership is transformational with a democratic approach, covering five key indicators: communication skills, teaching skills, classroom management, decisiveness, and exemplary behavior. Student morality is categorized as good, reflected in honest, disciplined, polite, respectful, and responsible behavior. Simple linear regression analysis shows that teacher leadership has a significant influence on student morality, contributing 96.5%